2016
DOI: 10.1111/clr.12814
|View full text |Cite
|
Sign up to set email alerts
|

Dental implant surface chemistry and energy alter macrophage activation in vitro

Abstract: The combination of high-energy and altered surface chemistry present on TiZr modSLA was able to influence macrophages to produce the greatest anti-inflammatory microenvironment and reduce extended pro-inflammatory factor release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 39 publications
3
85
0
Order By: Relevance
“…Furthermore, this is the first reported use of these transcortical implants custom‐made to fit rat femurs. Scanning electron microscopy, laser confocal microscopy, and x‐ray photoelectron spectroscopy revealed a surface morphology, average surface roughness, and surface composition similar to what has been previously reported for implants processed in the same manner …”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, this is the first reported use of these transcortical implants custom‐made to fit rat femurs. Scanning electron microscopy, laser confocal microscopy, and x‐ray photoelectron spectroscopy revealed a surface morphology, average surface roughness, and surface composition similar to what has been previously reported for implants processed in the same manner …”
Section: Discussionsupporting
confidence: 81%
“…At the micron level, blasting and etching produces a severely pitted surface and subsequent storage in saline not only results in a hydrophilic surface (modSLA), but also the spontaneous formation of nanoscale sized surface structures (Wennerberg, Svanborg, Berner, & Andersson, ). These features have been shown by our group (Alfarsi et al, ; Hamlet et al, ) and others (Hotchkiss et al, , ; Lu & Webster, ; Lü et al, ) to affect both the attachment of monocytes and macrophages, as well as the gene expression and secretion of pro‐inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 73%
“…Biomaterial features such as topography, particle size, porosity and ion release are all biomaterial-specific factors able to influence the immune response. Hydrophobic materials, for example, have been shown to enhance monocyte adhesion (Hezi-Yamit et al, 2009), whereas hydrophilic or neutral surfaces can inhibit macrophage adhesion but enhance the release of pro-inflammatory cytokines and chemokines (Alfarsi et al, 2014;Hamlet et al, 2012;Hotchkiss, Ayad, Hyzy, Boyan, & Olivares-Navarrete, 2017;Hotchkiss et al, 2016;Jones et al, 2007). More recently, a hydrophilic titanium surface with nanotopography (modSLA) has been shown to modulate the early inflammatory response in vivo promoting polarization of macrophages to an M2-like phenotype, even in diabetic conditions where an exaggerated pro-inflammatory environment is a distinguishing feature (Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is now understood that surface properties modulate immune cell function and factors produced by macrophages influence osteogenesis [26, 27]. Others have shown that osteocytes make direct contact with the implant surface, suggesting their importance in maintaining healthy bone remodeling as well as the longevity of implant osseointegration [28, 29].…”
Section: Discussionmentioning
confidence: 99%